PEMODELAN KEPUASAN PASIEN MENGGUNAKAN KUALITAS PELAYANAN KESEHATAN PADA RUMAH SAKIT UMUM MUHAMMADIYAH KOTA METRO - Suharto Suharto (Derivatif : Jurnal Manajemen, 2015)
ABSTRACT This study aims to (1) determine the effect the reliability of customer satisfaction, (2) the effect of responsiveness to customer satisfaction, (3) identify and analyze the influence of empathy towards customer satisfaction, (4) identify and analyze the influence of the reliability of the empaty, (5 ) identify and analyze the influence responsiveness to empaty. The method used is quantitative method, test hypotheses and path analysis. Based on research that has been done can be concluded that the results of the study found that the variable reliability, positive effect on customer satisfaction. Variable responsiveness positive effect on customer satisfaction.Variable empaty positive effect on customer satisfaction.Variable reliability, a positive direct effect on empathy.Variable responsiveness positive effect on empathy. The implication of this study is an attempt to repair the infrastructure, improve the reliability of employees when serving patients, responsive to the wishes of patients, providing assurance of service time, and give attention personally sincere empathy and understand consumer desires.Keywords: reliability, responsiveness, empathy, customer satisfaction.